Comparison of conventional LQR and LMI based LQR controller performance on the DC-DC Zeta converter with parameters uncertainty - Sarkawi, Hafez; Yoshito, Ohta (2017)
This paper presents the dc-dc zeta converter control. In order to cope with parameters uncertainty, the convex polytope modeling of the dc-dc zeta converter is introduced. To regulate the dc output voltage, the linear matrix inequality (LMI) is formulated based on linear quadratic regulator (LQR) problem to find the state-feedback gain for the convex polytope model. Simulation results are presented to compare the transient responses between conventional LQR and LMI based LQR. The result shows that the LMI based LQR can cope with high parameter uncertainty compared to the conventional LQR. The trade-off however is the high ripple presents in the control duty-ratio.